Giving dates to pregnant women as an efforts to increase hemoglobin levels - Miratu Megasari; Ani Trianab (Peneliti Teknologi Teknik Indonesia, 2022)
Anemia of pregnancy is a maternal condition with hemoglobin (Hb) levels <11 g% in the I and III trimesters or hemoglobin (Hb) levels below 11 g% in the I and III trimesters or levels < 10.5 g% in the second trimester. Anemia in pregnant women has a negative impact on both the mother and the fetus. Adverse effects on the mother are the occurrence of premature birth, low birth weight babies, infant mortality, time of parturition due to lack of uterine propulsion. Based on the author's experience when providing guidance to midwifery students who practice midwifery clinics, there are still pregnant women who do not take blood-boosting tablets because the side effects of these tablets are nausea, black bowel movements. So the mother is lazy to consume the blood-boosting tablet. The results of research regarding offering dates to pregnant women with mild anemia found that the average hemoglobin level of pregnant women before being given dates was 9.17 gr% with a standard deviation of 0.83gr%. While the average hemoglobin level of pregnant women after being given dates is 10.15gr% with a standard deviation of 0.800 gr%. The difference value before and before being given fruit is -0.983 with a standard deviation of 0.278. The results of the statistical test value of 0.001 means that there is a significant difference between Hb levels before and before being given dates. Giving dates to pregnant women as an effort to increase hemoglobin levels has been scientifically proven, therefore it is necessary to do community service by targeting a group of first trimester pregnant women who experience mild anemia and will be offered dates for 3 months at the Arrabih Pratama Clinic. After giving knowledge and offering dates to 10 pregnant women, they got changes and increases in hemoglobin levels ranging from 0.5 to 1.5 g%. It is expected to present dates that can be used as a method of midwifery care for pregnant women for the prevention of anemia.